Сто лет пути: [роман] / Т. В. Устинова - Устинова Татьяна Витальевна (Русский бестселлер, 2015)
Экземпляры: Дебинская биб-ка (20181224) / Инвентарный номер: 45233 / Цена: 145 / Сис.шифр: Р 2 / Авт.знак: У 80 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)